2019
DOI: 10.1101/515445
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Phage-encoded cationic antimicrobial peptide used for outer membrane disruption in lysis

Abstract: Spanins are required for the last step in bacteriophage lysis: the disruption of the outer membrane. Bioinformatic analysis has shown that ~15% of phages lack a spanin gene, which suggests an alternate mechanism of outer membrane disruption. To address this, we selected virulent podophage ϕKT as a spaninless exemplar and tested ϕKT genes for outer membrane disruption during lysis. Hypothetical novel gene 28 causes outer membrane disruption when coexpressed with ϕKT lysis genes and complements the lysis defect … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 33 publications
0
4
0
Order By: Relevance
“…It was recently suggested that phages lacking spanins (spaninless phages) need additional gene products that behave similarly to AMPs to induce efficient host cell lysis ( 67 ). This hypothesis could also be extrapolated to the presence of AMP-like membrane-permeabilizing subdomains, which could then compensate for a missing spanin system.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It was recently suggested that phages lacking spanins (spaninless phages) need additional gene products that behave similarly to AMPs to induce efficient host cell lysis ( 67 ). This hypothesis could also be extrapolated to the presence of AMP-like membrane-permeabilizing subdomains, which could then compensate for a missing spanin system.…”
Section: Resultsmentioning
confidence: 99%
“…There are indeed abundant examples in on May 2, 2021 by guest http://jvi.asm.org/ Downloaded from literature on the ability of G-lysins to interact with bacterial membranes and permeabilize them (33,38,39,69), a trait that, it is plausible to say both from our own analysis and the experimental results of many works, would reside in such AMP-like elements. It has been recently suggested that phages lacking spanins ('spaninless phages') need additional gene products that behave in a similar way to AMPs to induce efficient host cell lysis (70). This hypothesis could also be extrapolated to the presence of AMP-like, membrane permeabilizing subdomains, which could then compensate for a lacking spanin system.…”
Section: Downloaded Frommentioning
confidence: 99%
“…Viruses harbor vast potential for diverse genetic content, arrangement, and encoded functions [14][15][16][17]. Recognizing their genetic diversity, there has been substantial interest in "mining" these viral sequences for novel anti-microbial drug candidates, enzymes for biotechnological applications, and for bioremediation [18][19][20][21][22]. Recently, it has been appreciated that viruses may directly link biogeochemical cycling of nutrients by specifically driving metabolic processes [23][24][25][26][27].…”
Section: Introductionmentioning
confidence: 99%
“…Annotations from all three databases are used to assemble 27 metrics for the neural network classifier. Briefly the metrics are as follows: [1] total proteins, [2] total KEGG annotations, [3] sum of KEGG v-scores, [4] total Pfam annotations, [5] sum of Pfam v-scores, [6] total VOG annotations, [7] sum of VOG v-scores, [8] total KEGG integration related annotations (e.g., integrase), [9] total KEGG annotations with a v-score of zero, [10] total KEGG integration related annotations (e.g., integrase), [11] total Pfam annotations with a v-score of zero, [12] total VOG redoxin (e.g., glutaredoxin) related annotations, [13] total VOG non-integrase integration related annotations, [14] total VOG integrase annotations, [15] total VOG ribonucleotide reductase related annotations, [16] total VOG nucleotide replication (e.g., DNA polymerase) related annotations, [17] total KEGG nuclease (e.g., restriction endonuclease) related annotations, [18] total KEGG toxin/anti-toxin related annotations, [19] total VOG hallmark protein (e.g., capsid) annotations, [20] total proteins annotated by KEGG, Pfam and VOG, [21] total proteins annotated by Pfam and VOG only, [22] total proteins annotated by Pfam and KEGG only, [23] total proteins annotated by KEGG and VOG only, [24] total proteins annotated by KEGG only, [25] total proteins annotated by Pfam only, [26] total proteins annotated by VOG only, and [27] total unannotated proteins. Non-annotation features such as gene density, average gene length and strand switching were not used because they were found to decrease performance of the neural network classifier despite being differentiating features between bacteria/archaea and viruses; viruses tend to have shorter genes, less intergenic space and strand switch less frequently.…”
Section: Non-neural Network Steps and Assembly Of Annotation Metricsmentioning
confidence: 99%